MODERN SLAVERY IN THE MEMOIR HIDDEN GIRL BY SYIMA HALL: A REVIEW ON THE MAIN CHARACTER - Mutiara Magdalena; Agnes Setyowati H; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
AbstractThe main topic in this research is modern slavery which is examined based on the study of the main character in Shyima Hall’s memoir: Hidden Girl. The process of this research involves the overall story, intrinsic elements: character and characterization, conflict, setting, and symbol, as well as extrinsic elements: perspective of cultural studies focusing on class and the understanding of modern slavery. This qualitative research is conducted by applying descriptive analysis method along with library research technique, leading to the identification that class turns out to be the cause of modern slavery. The main character, Shyima, undergoes three forms of modern slavery: human trafficking, domestic slavery and child slavery. These experiences eventually forms her determination to fight against modern slavery individually, by becoming an anti-modern slavery activist.Keywords: class, main character, modern slavery, slavery